Exploring the Possibility of Implementing Telecommuting at University Utara Malaysia - Haitham Hamad, El-Rashdan (2004)
Global technology has quickly progressed to provide more accessible business modes of Communication. The image of the traditional workplace as a particular place to go to work is being replaced with employees working wherever they can be most efficient and productive, whether at home, on a plane, on the road, or a telework center. The availability of affordable technology has been one of the major contributors to the “any time, any place” telecommuting trend. The purpose of this study is investigate the possibility of the implementation of the teleworking at University Utara Malaysia (UUM), the suitable selection job criteria, the suitable technology needed to support this new mode of business, the employee perception of willingness to telecommute, and top management support, to investigate the possibility of a lecture job to be a telecommute, we adopt Jack Nilles Job task analysis, for the technology factor, data will be collected through content analysis, structured interview will be done with top management to determine their willingness to implement this program, and questionnaire will be used to identify the UUM lecturers willingness to telecommute. This study found that technology factor is available, people are willing to telecommnute, lecturer job is suitable, and management is agreeable, so people can enjoy telecommuting benefits if there is an established policy and regulations that allow them to telecommute.